ANALISIS KONTRASTIF UNSUR GRAMATIKAL IKLAN MOBIL DI JEPANG DAN IKLAN MOBIL DI INDONESIA PADA MEDIA TELEVISI - Ni'mah, Dina; Ratna, Maharani; Rosliana, Lina (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Diponegoro, 2016)
The author chooses this title because both of the car advertisement eitherIndonesia or Japan version are equally a product of Toyota, but have different wayin delivery. The writer wants to know the message contained in the advertisementof Japan and Indonesia versions.The methods that used in this thesis are descriptive and contrastive. First, thewriter collected the data from youtube to listen the advertisement conversation andthen record the text. The writer uses contrastive analysis to analyze Indonesia andJapan advertisement. After that the writer comes into the presentation of results.The grammatical elements contained in Japan and Indonesia advertisement are thesame which both of them have the reference, substitution, ellipsis, and conjunction.Both of the advertisement have different message, the message of Japanadvertisement is the Japanese people should drive a car again of course usingToyota product. Meanwhile, the Indonesia advertisement shows how great andcomfort using car from Toyota product.